2019
DOI: 10.1681/asn.2019040371
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Cystinotic Mice by Kidney-Specific Megalin Ablation Supports an Endocytosis-Based Mechanism for Nephropathic Cystinosis Progression

Abstract: BackgroundDeletions or inactivating mutations of the cystinosin gene CTNS lead to cystine accumulation and crystals at acidic pH in patients with nephropathic cystinosis, a rare lysosomal storage disease and the main cause of hereditary renal Fanconi syndrome. Early use of oral cysteamine to prevent cystine accumulation slows progression of nephropathic cystinosis but it is a demanding treatment and not a cure. The source of cystine accumulating in kidney proximal tubular cells and cystine’s role in disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…in other proximal tubular defects characterized by low-molecular-weight proteinuria, such as Lowe syndrome and Dent disease. 50 In addition, lack of megalin expression may also indicate cell dedifferentiation, as shown in mPTCs by Raggi et al 21 Therefore, and irrespective of the underlying mechanism, restored expression of megalin after in vitro and in vivo treatments in our experimental settings indicates that luteolin may be efficient in treating the renal Fanconi syndrome of cystinosis and is not at odds with the report by Janssens et al 49 In conclusion, luteolin was selected from the positive hits of an HTS aimed at improving autophagy because of its additional effects on oxidation, apoptosis, and inflammation, all of which are altered in cystinosis. [8][9][10][11][14][15][16][17]32,45,[51][52][53] Moreover, luteolin belongs to the flavonoid family, similar to genistein, which we recently showed to ameliorate lysosomal cystine content and lysosomal compartment distribution in cystinosis, likely through stimulation of the TFEB pathway.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…in other proximal tubular defects characterized by low-molecular-weight proteinuria, such as Lowe syndrome and Dent disease. 50 In addition, lack of megalin expression may also indicate cell dedifferentiation, as shown in mPTCs by Raggi et al 21 Therefore, and irrespective of the underlying mechanism, restored expression of megalin after in vitro and in vivo treatments in our experimental settings indicates that luteolin may be efficient in treating the renal Fanconi syndrome of cystinosis and is not at odds with the report by Janssens et al 49 In conclusion, luteolin was selected from the positive hits of an HTS aimed at improving autophagy because of its additional effects on oxidation, apoptosis, and inflammation, all of which are altered in cystinosis. [8][9][10][11][14][15][16][17]32,45,[51][52][53] Moreover, luteolin belongs to the flavonoid family, similar to genistein, which we recently showed to ameliorate lysosomal cystine content and lysosomal compartment distribution in cystinosis, likely through stimulation of the TFEB pathway.…”
Section: Discussionsupporting
confidence: 59%
“…48 In addition, the distribution of lysosomes normalized after treatment with luteolin in our cell models, most likely because of improved functionality, as indicated by mature cathepsin-D levels. Recently, Janssens et al 49 showed that inhibition of megalin-mediated endocytosis efficiently prevents accumulation of cystine and delays progression of kidney disease in Ctns 2/2 mice. In these experiments, ablation of megalin was used as a strategy to block uptake of proteins, whose degradation further increases cystine contents in Ctns 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of endocytic function and PTC differentiation in Ctns −/− mice might temporally precede apoptosis and the development of swan-neck deformity [10]. However, blocking the uptake of disulfide-rich plasma proteins through inhibition of megalin-mediated endocytosis efficiently prevented the accumulation of cystine and delayed progression of kidney disease in Ctns −/− mice [27].…”
Section: Oxidative Stress Leading To Mitophagymentioning
confidence: 99%
“…This difference in timing may reflect a greater resolution of disease progression in mice and could be exploited to better understand the molecular changes governing the transition from dysfunctional transport activity to tubular atrophy. It should also be noted that subsequent publications by different groups using the C57BL/6 Ctns -/- mice have reported varying degrees of Fanconi syndrome, from mild/incomplete to nonexistent [ 110 ]. This variation may be due to inbreeding at different facilities.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…These observations help establish a model of cystinotic kidney damage in which (1) cystine accumulation causes lysosomal and autophagic dysfunction, (2) the failure to clear defective mitochondria results in increased oxidative stress (sensitizing the cell to apoptosis), and (3) compensatory proliferation and dedifferentiation induces Fanconi syndrome, compromised epithelial integrity and tubular atrophy. A key protein facilitating this process in proximal tubule cells is LRP2, the multiligand receptor that is responsible for the endocytosis of filtered proteins including albumin, which is cystine rich due to several disulphide bonds [ 110 ]. Deleting LRP2 in C57BL/6 Ctns -/- mice via a conditional Cre/Lox approach prevents cystine accumulation, crystal deposition, apical dedifferentiation in the kidney, and the subsequent formation of “swan neck” lesions [ 110 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%